Ayapana sprucei (Asteraceae: Eupatorieae), a new combination and the correct name for A. elata from Central and South America - Wei, Xiao-Mei; Hu, Ying; Huang, Bao-You; Peng, Yu-De; Zhu, Yan-Xia; Ning, Shan; Ma, Zhong-Hui (Phytotaxa, 2025)
N/A